Depression Preceding Diagnosis of Bipolar Disorder - O'Donovan, Claire; Alda, Martin (Frontiers in Psychiatry, 2020)
This paper focuses on depression that precedes an onset of manifest bipolar disorder. First, we reviewed the clinical characteristics of patients presenting with an episode of depression who subsequently developed episodes of mania or hypomania. Such features can be helpful clinically in estimating whether a patient might be suffering from bipolar disorder. The existing literature shows a strong consensus: depression with early onset and recurrent course with multiple episodes, subthreshold hypomanic and/or mixed symptoms, and family history of bipolar disorder or completed suicide have been shown by multiple authors as signs pointing to bipolar diagnosis. This contrasts with relatively limited information available to guide treatment of such “pre-bipolar” patients, especially those in the adult age range. Antidepressants are still the most common pharmacological treatment here, but clinicians need to be aware of their potential risks. In some patients with unrecognized bipolar depression, antidepressant can not only produce switch to (hypo)mania, but also mixed symptoms, or worsening of depression with an increased risk of suicide. In the future, genetic research could make the identification of bipolar depression easier by generating informative markers and polygenic risk scores.